Analysts’ disagreement, self-selection, and stock returns - Wu, Liang; Long, Yunshen; Li, Wenyue; Wu, Bingyan (Journal of Business Economics and Management, 2023)
Two ex-ante variables are introduced to characterize the analysts’ biased behavior, namely the analysts’ disagreement and self-selection in analysts’ earnings forecasts. The study investigates the impact of the analysts’ disagreement and self-selection on the stock returns. A theoretical analysis derives how the stock returns are correlated with the two variables. There are two channels through which the stocks are priced according to the analysts’ disagreement. The first one is the risk channel as the analysts’ disagreement is associated with earnings uncertainty. The stock price will be discounted before the actual earnings announcement. The second one is the optimistic bias channel. The optimistic bias channel means that the stock is overpriced if the investors do not correct the analysts’ bias. The self-selection is negatively correlated with the stock return through the optimistic bias channel as more self-selection means more optimistic bias as low forecasting values are not revealed. The empirical analysis using data from the Chinese stock market supports the theoretical conclusion.